Concordance of CCR5 genotypes that influence cell-mediated immunity and HIV-1 disease progression rates (2011)
We used cutaneous delayed-type hypersensitivity responses, a powerful in vivo measure of cell-mediated immunity, to evaluate the relationships among cell-mediated immunity, AIDS, and polymorphisms in CCR5, the HIV-1 coreceptor. There was high concordance between CCR5 polymorphisms and haplotype pairs that influenced delayed-type hypersensitivity responses in healthy persons and HIV disease progression. In the cohorts examined, CCR5 genotypes containing -2459G/G (HHA/HHA, HHA/HHC, HHC/HHC) or -2459A/A (HHE/HHE) associated with salutary or detrimental delayed-type hypersensitivity and AIDS phenotypes, respectively. Accordingly, the CCR5-D32 allele, when paired with non-?32-bearing haplotypes that correlate with low (HHA, HHC) versus high (HHE) CCR5 transcriptional activity, associates with disease retardation or acceleration, respectively. Thus, the associations of CCR5-?32 heterozygosity partly reflect the effect of the non-?32 haplotype in a background of CCR5 haploinsufficiency. The correlations of increased delayed-type hypersensitivity with -2459G/G-containing CCR5 genotypes, reduced CCR5 expression, decreased viral replication, and disease retardation suggest that CCR5 may influence HIV infection and AIDS, at least in part, through effects on cell-mediated immunity. © The Author 2011. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. All rights reserved.